Pemanfaatan Aplikasi Berbasis Android Untuk Meminimasi Produk Return/”Retur” di Industri Retail - Wahyudin , Cucu; Ratna Gumilang, Risa (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The main process carried out by the retail industry is distribution. The distribution flow starts from receiving goods from suppliers by the receiving division, the picking process carried out by the warehouse division, sending goods to retailers carried out by the distribution and delivery division, as well as receiving returned/returned goods (unsold goods) from retailers by the returns division. The problem faced by the retail industry is the high value of returned products identified as inventory. From the results of problem identification using the six sigma method, it was found that the cause of the high inventory of returned products was the late arrival of returned goods from retailers. In general, returned goods can be returned to the supplier/manufacturer if the maximum expiration date is 3 months. If the expiration date is less than 3 months, the item cannot be returned/replaced with a new product. Delays are caused by the system for checking returned goods that are nearing their expiry date, which is still done manually, so there is no system that can warn retail employees to immediately return the returned goods. This problem can be avoided if there is a product identification system that will expire. This identification system is called an early warning system. Early signal system design uses the Structured Analyzed and Design Technique (SADT) design method. The operating system chosen is Android base. The use of the Android base was chosen because it is more effective and efficient for use in retail branches or retail industry outlets. The process of creating this early signal system uses a MySQL database. The application creation process uses PHP and Android Studio. With an early signal system, delays in returning goods by retailers can be minimized.